Experimental results of electromechanical structure properties of noise and vibration on power transformers after lightning impulse test. (January 2022) - Hsu, Chang-Hung
Abstract: Transformer damage due to lightning impulse wave may result in serious loss of profits, thereby compromising the reliability of power systems. Currently, there is limited studies on the effect of lightning impulse on the noise and vibration of power transformers. In line with this, this study proposed a single-phase transformer with a voltage specification of 345 kV (high voltage)/115 kV (low voltage) and a capacity of 200 MVA. The soft magnetic 27PH100 material with a low magnetostriction variation was selected as the core material for the design of a transformer with a significantly low noise and vibration that could be maintained even after repeated lightning impulse applications. First, the parameters of the core and coil with k-factor design of the transformer, which can withstand high electrical signals, such as lightning impulses and insulation damage, was established and tested. The deformation and modal shape of the core and winding were simulated by finite element analysis. Furthermore, sweep frequency response analysis was used to observe the structure of the core and coil without any deformation. Diagnosis gas analysis was adopted to analyze the oil in the tank of the transformer to avoid dielectric loss due to insulation damage. Temperature rise test was also used to verify the stability of the transformer performance under no-load and full-load conditions. Finally, the results of the continuous lightning impulse tests revealed that the transformer operated under a stable performance, while generating significantly low noise (<65 dB) and vibration (<10 μm), which are remarkably lower than the IEEE standard of 85 dB.